Analisis Pengakuan Pendapatan Dan Beban Jasa Kontruksi Berdasarkan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada PT PUKS Ujunggading Kab. Pasaman Barat - Nur Ainun; Hendra Harmain; Nuri Aslami (Universitas Katolik Widya Karya Malang, 2023)
.This research aims to determine the Analysis of Recognition of Revenue and Expenses for Construction Services Based on Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) at PT PUKS Ujunggading District. West Pasaman. This research uses a qualitative approach with descriptive methods. Data collection techniques using interview techniques and document study. This research uses data collection techniques by interviewing employees in the administration and finance fields and documents regarding financial reports. The results of this research indicate that the implementation of Income Recognition and Expense Recognition at PT PUKS Ujunggading Regency. West Pasaman is in accordance with SAK ETAP with the level of conformity of income recognition of PT PUKS Ujunggading Kab. West Pasaman against SAK ETAP 75% and the level of suitability of expense recognition for PT PUKS Ujunggading Kab. West Pasaman towards SAK ETAP 80% which is recognized in the 2021 profit and loss statement. PT PUKS Ujunggading Kab. West Pasaman is guided by SAK ETAP in preparing its financial reports because it will make the job easier and minimize errors in recording. Impact of Income Recognition and Expense Recognition at PT PUKS Ujunggading Regency. West Pasaman is in accordance with SAK ETAP with a conformity level of 72%. There are errors in the income statement regarding other income and other expenses, the amount of which is unknown and not recorded. This has an impact on the profit and loss report which can create inaccuracies due to empty accounts. In the cash flow report there is no funding activity, whereas in the previous year's cash flow report the funding activity itself is known at what nominal value, this could have an impact on the cash flow report of PT PUKS Ujunggading Kab. West Pasaman because it can create inaccurate reports.